VISUALISASI BUDAYA SUNDA DALAM KOMIK MAD HURI DAN SI BOGEL PADA MAJALAH MANGLÃ‰ - Setia Surya Kusumah (ARTic, 2018)
The comic strip of â€œMad Huriâ€ and â€œSi Bogelâ€ are comics found inside Mangle magazine. Those comics tell about Sundanese story and its cultural backgrounds. The research study those comic strips which aims to find out the uniqueness of their visualizations, image and story-telling style using visual language as the structure of visual communication. The methodology used was Primadi Tabrani visual language analysis. The methodology explained how an object can explain its message through the image contents (Isi Wimba), the image way (Cara Wimba), and its grammar so it can tell the story. From the research it was concluded that â€œMad Huriâ€ and â€œSi Bogelâ€ comic strips had unique Sundanese characteristics supported by the image contents (Isi Wimba) in accordance with the stereotypes of Sundanese society on the characteristics of their figures based on their outfits and Sundanese attributes, face posture and body shapes, and levels on society. The background of the image caught the Sundanese natural environment such as the uniqueness of architectural. Moreover, the comic strips showed a leuit and a lisung which meant that Sundanese people were still preserve their culture as their system of technology. The image way with the natural point of views communicated the social levels of the upper and the lower social classes (menak and somah) and Sundanese etiquette. Stylized depiction caught the reality of Sundanese culture in real situation. The inner grammar showed the uniqueness of gesture in Sundanese people such as emok, sila tutug, honorary behaviors that show the relationships on how a personal attribute can affect gestures. The outer grammar on the frequency of appearance showed that those comics were affected by traditional story telling.